10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Despite well-documented barriers to ophthalmic services, ophthalmic care delivery among incarcerated populations remains understudied. This prospective observational study aimed to characterize ophthalmic referral patterns, triage timelines, and follow-up attendance among incarcerated individuals referred to a tertiary eye care center (July 1, 2024 to July 1, 2025). On-call ophthalmology residents assigned referrals to standardized triage categories based on urgency. Referral and clinical data were extracted to evaluate wait times, triage delays, and follow-up attendance. Of 56 referrals, 48 patients (65 eyes) completed an initial visit. Trauma was the most common indication (37.5%). Most referrals were assigned high-priority triage (≤24 hours: 27.1%; ≤48 hours: 33.3%). Median wait time increased with decreasing triage priority (p < 0.001), with longer delays for lower-priority triages (p = 0.002). Follow-up was more frequently requested for trauma (66.7%) versus nontrauma (26.7%; p = 0.002). Among those scheduled for repeat appointments, 44.4% were lost to follow-up, more commonly among trauma (33.3%) versus nontrauma (6.7%; p = 0.040). Despite appropriate triage, lower-priority cases experienced delays beyond triage targets. The high rate of loss to follow-up among patients with ocular trauma, who may require complex ongoing care, highlights the need for improved continuous ophthalmic care access.